A low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire and a manufacturing method thereof
By using the low-carbon high-strength compound heat rolling bar with the C-SI-Mn composition, combined with the temperature treatment and equal warming of the online melting salt weak quenching, the intensity and tissue uniformity after reducing the carbon content in the existing technology will be solved. It is difficult to take into account the effects of high intensity, low cost, and low -cut risks.
Patent Information
- Application Number
- CN202411356384.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-09-27
AI Technical Summary
After reducing the carbon content of the existing hot-rolled strips for 1860MPa grade steel strands, the strength and tissue uniformity are difficult to take into account, and the addition of hardenable elements increases the manufacturing cost, resulting in a high risk of wire breaking.
The low-carbon, high-strength compound hot rolling bars designed with the C-SI-MN ingredients, and through the temperature treatment of the weak quenching of online salt, so that the bars can quickly enter the benhered and pearl mixed phase area to form a quenching shellite and cable. The genetic compound tissue, and through the process of warming the warming and the cold cold, regulates the structure of the tissue structure and the strong plasticity.
While reducing the carbon content, the intensity and tissue uniformity of the bars are improved, the risk of disconnection is reduced, and the cost of material is lower, and the mechanical performance fluctuates less.
Smart Images

Figure CN118854172B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods for stranded wires, and specifically relates to a low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa-grade stranded wires and a manufacturing method thereof. Background Art
[0002] At present, domestic 1860MPa grade steel strands are mainly made of alloy hot-rolled wire rods with a carbon content of 0.82% that are cold-drawn, twisted and braided. As raw materials, hot-rolled wire rods directly affect the cost, processing and performance of finished steel strands. Once the carbon content is reduced to 0.76% or even below, the product strength will drop sharply. At the same time, with the continuous increase in the demand for drawing speed and surface reduction rate in steel strand manufacturing, it brings greater challenges to improving the performance of hot-rolled wire rods for 1860MPa grade steel strands with reduced carbon content.
[0003] The high carbon steel wire rod as the parent material of steel strand is generally pearlite steel. The existing hot-rolled wire rod with reduced carbon content for 1860MPa grade steel strand is mainly rolled and controlled by Stelmor air cooling after rolling. In order to make up for the strength loss caused by reducing the carbon content, it is also necessary to add elements such as Cr, Mn, B to improve the hardenability, so as to improve the ability of the wire rod to obtain fine pearlite structure, i.e., sorbite, under low-speed cooling and low temperature. The higher the sorbitization rate, the more suitable the wire rod is for drawing. For example, the low-carbon, high-strength and high-toughness steel strand wire rod and its production process disclosed in patent CN104789880B adopts C-Si-Mn-Cr-B composition design combined with Stelmor first fast and then slow cooling to obtain sorbite ≥ 90% wire rod, achieving tensile strength Rm ≥ 1200MPa and cross-sectional shrinkage Z ≥ 34%. However, the hot-rolled wire rod with lower manufacturing cost, higher strength and uniformity of structure and better plasticity still has the following technical difficulties:
[0004] First, the addition of alloying elements such as Cr and B increases the manufacturing cost. For the purpose of reducing costs, omitting Cr and B components will reduce the hardenability of the wire rod. Under air cooling conditions, the phase transformation curve moves accordingly, which is not conducive to the refinement of cementite lamellae and will bring about a large loss of strength. Si, as a strengthening element of ferrite, can play a role in solid solution strengthening, but it will also shift the CCT curve to the right, prolonging the incubation period and transformation time during the phase transformation process. The minimum cooling capacity of the Stelmor air cooling line is limited. The time that the wire rod passes through the pearlite phase transformation temperature range during the continuous cooling process is relatively short, which is not conducive to the full incubation of troostite, resulting in limited strength improvement and decreased drawing performance. Even in the subsequent slow cooling process, the plasticity is significantly deteriorated and the performance fluctuation is increased due to the transformation of retained austenite into abnormal martensite structure.
[0005] Second, with the increase of C, Mn, and Cr elements, positive segregation is easily formed in the center of the billet. Secondary cementite is easily precipitated along the austenite grain boundary during the cooling process after rolling. As the residence time in the precipitation temperature range is prolonged, more secondary cementite will be precipitated and connected to form a network, which will destroy the uniformity of the organization and significantly deteriorate the drawing performance of the wire rod. In addition, a large amount of tertiary cementite will be precipitated, and the cementite carbide will coarsen, weakening the strengthening effect of carbon. In order to minimize the influence of network carbon and improve the strength of the wire rod, the Stelmor cooling before the phase change will adopt strong air cooling treatment. However, on the one hand, the maximum cooling capacity of air cooling is limited. Under the influence of segregation, network carbon and cementite carbide coarsening will still exist, affecting the uniformity of the organization and mechanical properties. As the drawing deformation increases, the crack propagates and causes wire breakage; on the other hand, Although the pearlite and bainite phase transformation zones are separated by increasing the hardenability of the wire rod, due to the influence of segregation and the uncontrollability and fluctuation of air volume, wind speed and wind temperature increase with the increase of wind cooling intensity, the different stacking density of the wire rod on the roller will further increase the temperature difference between the windward side and the leeward side of the wire rod, causing some positions to be transformed into bainite or martensite structures that deteriorate the drawing performance at a lower temperature, resulting in a high risk of abnormal tissue, uncontrollable precipitation, and large performance fluctuations. With the increase of subsequent cold drawing speed and area reduction rate, the risk of wire breakage during stranded wire drawing is higher. In order to reduce the cooling gradient from the outside to the inside on the wire rod cross section, the cooling intensity is appropriately reduced to make the sorbitization rate inside and outside the wire rod more uniform, which will make the sorbitan lamellae coarser and reduce the overall strength.
[0006] 3. In order to improve the strength of wire rod, Stelmor wire increases the troostitization rate by reducing the phase transformation cooling rate, but the coarse cementite layer will increase the softening difficulty. After continuous cooling treatment, the wire rod is in a low temperature state after phase transformation, and the tissue stress and dislocation density are high, and the plastic deformation resistance is large. The risk of wire breakage is high during the manufacture of stranded wire; although adding bainite or martensite to the tissue can improve the strength of wire rod, for example: Patent CN117004883A discloses a high-strength and high-ductility prestressed steel wire / stranded wire Hot-rolled wire rod and production method, using C-Si-Mn-Cr components combined with low-temperature spinning, obtains a structure dominated by bainite with a small amount of residual austenite and martensite under salt bath isothermal at Ms point temperature ±20°C, but the isothermal temperature is low and the thermal power is insufficient, which will lead to the formation of bainite and martensite structure distortion and high dislocation density, high wire rod brittleness, resulting in stranded wire cold drawing and even wire rod winding, transportation, winding and unwinding process breakage, resulting in raw material consumption, affecting the cost and yield rate of wire rod and steel wire. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a low-carbon and high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire and a manufacturing method thereof, which reduces the carbon content while further simplifying the composition, improving the uniformity of the structure and the strength of the wire rod, while taking into account the higher plasticity of the wire rod, and is used to adapt to the production of 1860MPa grade stranded wire and reduce the risk of wire breakage.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for manufacturing a low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire, the manufacturing method comprising:
[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.70%~0.74%, Si: 0.5%~0.65%, Mn: 0.72%~0.84%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥920°C, it is subjected to an online molten salt weak quenching isothermal treatment to make the wire rod cool at a cooling rate of ≥38°C / s The temperature is lowered from the austenite state into the mixed phase region of bainite and pearlite, forming a structure dominated by quenched bainite and troostite duplex phase. At the same time, isothermal tempering is performed to promote the tempering softening of quenched bainite and troostite, and induce the melting transformation of some troostite lamellae. Finally, it is slowly cooled by rollers to obtain a hot-rolled wire rod with a microstructure including 62% to 68% tempered troostite by volume, 26% to 33% tempered bainite by volume, and the rest being a duplex structure composed of ferrite and fused troostite.
[0011] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:
[0012] (1) Carbon: C is a basic strengthening element in carbon steel and is cheaper than other alloying elements. It can increase the volume fraction of cementite strengthening phase in tempered troostite structure, which is beneficial to the formation of refined troostite lamellar structure and the reduction of melting and tempering softening difficulty. However, too high C content will promote central segregation during alloy solidification, increase decarburization and the precipitation tendency of brittle proeutectoid cementite, and thus reduce the connectivity between grain boundaries and affect fatigue performance. Therefore, in order to take into account the high strength of 1860MPa grade stranded wire and reduce the difficulty of controlling the uniformity of wire rod structure, it is selected to appropriately reduce the carbon content. Using low carbon content to reduce component segregation is more conducive to isothermal refinement of cementite carbides by weak quenching of molten salt, so as to improve the strengthening effect and compensate for the strength loss. At the same time, it can regulate the peak precipitation temperature of troostite and bainite, and is more convenient to simultaneously regulate the quenched bainite and troostite phase transformation through salt bath treatment in the mixed phase zone and simplify the process flow. Therefore, the mass percentage of C is controlled to be 0.70%~0.74%.
[0013] (2) Silicon: Si is often added to molten steel as a deoxidizer during the smelting process. As a solid solution strengthening element, it can shift the CCT curve to the right, obtain a finer troostite structure at the same cooling rate, and improve the strength. At the same time, it can inhibit the coarsening of cementite and accelerate the diffusion rate of carbon, which is beneficial to improve the isothermal softening rate of quenched bainite and troostite. However, too high silicon will increase the decarburization tendency, excessively prolong the transformation time during the phase transformation process, reduce the toughness of the steel, and is not conducive to the deep cold drawing of stranded wire manufacturing. Therefore, on the basis that molten salt weak quenching isothermal cooling can be used for a longer time than Stelmor cooling to meet the full incubation of the complex phase structure, in order to improve the high strength of the stranded wire rod and reduce the difficulty of tempering softening, the Si content is appropriately increased, and the mass percentage of Si is controlled to be 0.5%~0.65%.
[0014] (3) Manganese: Mn is often added as a deoxidizer in the steelmaking process. As an austenite stabilizing element, it can increase the strength of steel and reduce the phase transformation temperature. It is more convenient to quickly skip the secondary and tertiary cementite peak precipitation temperatures during online molten salt weak quenching isothermal, and enter the pearlite and bainite mixed phase area to form a troostite structure with fine lamellar spacing and a small amount of quenched bainite, thereby improving the matrix strength. However, when the Mn content is too high, it will cause the central alloy element segregation of the steel billet, increase the hardenability of the wire rod core, increase the risk of martensite precipitation in the wire rod core, reduce the diffusion activity of carbon, affect the softening efficiency of quenched bainite and troostite, and reduce the drawing performance of the wire rod. Therefore, in order to take into account the high strength and toughness combination of stranded wire steel wire rod, minimize the difference in the distribution of the wire rod structure from the outside to the inside, and facilitate the structure control, the mass percentage of Mn is controlled to be 0.72%~0.84%.
[0015] (4) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0016] The hot-rolled wire rod adopts C-Si-Mn composition design, which has lower carbon content than 82B wire rod and does not contain Cr, B and other components than 72B-S wire rod, which can further reduce material cost. By optimizing the composition ratio of C, Si and Mn, the composition segregation is appropriately reduced, the hardenability of the wire rod is regulated, and the phase transformation temperature is lowered, which provides favorable conditions for refining cementite carbide and troostite lamellae, regulating the peak precipitation temperature of troostite and quenched bainite to be close, and then controlling the formation of complex phase structure with mixed phase area and reducing the difficulty of tempering. In terms of manufacturing method, a higher spinning temperature is selected to provide favorable conditions for obtaining a larger temperature gradient through online molten salt micro-quenching treatment:
[0017] 1. Compared with the existing Stelmor strong cooling process, the online molten salt micro-quenching treatment can utilize the high heat exchange capacity of molten salt to promote extremely rapid cooling of the wire rod, so that the wire rod can quickly pass through the ferrite phase transformation temperature range to avoid the formation of coarse ferrite, avoid staying in the precipitation temperature range of secondary and tertiary cementite, prevent the precipitation of network carbides, effectively reduce the network carbon level, improve the uniformity of the organization, reduce the peak precipitation of tertiary carburizing at 700~800℃, thereby refining the cementite carbonization, to improve the strengthening effect of carbon elements and matrix strength, and make up for the strength loss caused by reducing carbon content and eliminating hardenability components; at the same time, the molten salt is wrapped on the surface of the wire rod, and there is no influence of the wind side and the leeward side, which can promote uniform and rapid heat exchange of the wire rod, reduce the temperature gradient from the outside to the inside of the wire rod, avoid entering the martensite phase during the cooling process and transforming the high-temperature austenite into the abnormal martensite organization, and promote uniform phase transformation of the organization.
[0018] 2. Compared with the phase change control of the existing Stelmor cooling line, the phase change temperature of the present invention is lowered, the boundary of the troostite and bainite phase change temperature range, and the temperature of the mixed phase region is lower than that of the pearlite phase region. The wire rod quickly enters the bainite and pearlite mixed phase region from the high-temperature austenite state of high-temperature spinning, which can significantly increase the supercooling degree of the troostite transformation, and cooperates with Si to inhibit the coarsening of cementite, which is beneficial to promoting the nucleation of troostite, so that the troostite in the complex phase organization is mainly fine lamellar spacing. At the same time, compared with the existing Stelmor cooling due to the large fluctuation of the wire rod cooling rate and continuous cooling, which leads to insufficient transformation of austenite and uncontrollable bainite phase change, the wire rod of the present invention can In order to keep it consistent with the molten salt temperature, isothermal treatment is carried out in the mixed phase region for a longer time, and the high-temperature austenite in the wire rod is controlled to transform into troostite and quenched bainite at the same time, making the transformation of quenched bainite simpler and controllable. At the same time, the wire rod is transformed into a structure dominated by quenched bainite and troostite duplex phase to compensate for the adverse effect of increasing Si on the full incubation of troostite, so as to further reduce the proportion of ferrite, and use duplex phase structure control to compensate for the strength loss caused by reducing carbon content and eliminating elements such as Cr and B. At the same time, the matrix strength is further improved, and the residual austenite in the core is avoided to form abnormal martensitic structure during the subsequent roller slow cooling process.
[0019] 3. Compared with the phase change control of the existing bainite wire rod, the temperature of the mixed phase region is higher than that of the bainite phase region. The wire rod can maintain a relatively higher temperature under long-term isothermal treatment of molten salt weak quenching, so that the newly formed quenched bainite and troostite structures are tempered, the organizational stress and dislocation density are reduced, and some troostite lamellae are induced to melt and transform. After the quenched bainite is transformed into the tempered state, the strength characteristics can be retained and the brittle structure can be toughened. After the troostite is transformed from melting and spheroidizing to melting troostite and tempered troostite, the plasticity can be further improved. In the subsequent roller slow cooling process, the residual heat of the wire rod after leaving the salt bath can be further utilized, and the high-temperature tempering softening effect can be continued by slow cooling, so as to promote further toughening of the organization and improve the tempering softening effect, so as to regulate the wire rod organization and strength-plastic matching, so that the wire rod has better plasticity and organizational uniformity, and is less likely to break during the winding process than the bainite wire rod. At the same time, the better plasticity and toughness properties also make it less likely to break during cold drawing and wire making of the stranded wire.
[0020] Since the composition of the hot-rolled wire rod is simpler and the spinning temperature is relatively high, a higher heating temperature can be selected before rolling to promote the homogenization of the billet composition, while avoiding decarburization and growth of the original austenite crystals caused by excessively high heating temperature and excessively long time in the furnace. In a preferred embodiment, before rolling, the heating temperature of the heating furnace is controlled to be ≤1110°C and the time in the furnace is ≤4h.
[0021] Since the spinning temperature is relatively high, a higher rolling temperature can be selected to reduce deformation resistance, increase deformation and rolling speed, and avoid decarburization caused by excessively high rolling temperature. Appropriate rolling temperature and deformation distribution are selected, and the final rolling temperature is appropriately increased to increase the degree of recrystallization of deformed austenite, promote dynamic recrystallization during the final rolling process, and refine the grains for deformation strengthening. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1060~1085℃, the initial rolling reduction is 25%~33%, the final rolling temperature is ≥945℃, and the final rolling reduction is 28%~36%.
[0022] In a preferred embodiment, the molten salt temperature of the online molten salt weak quenching isothermal treatment is 425~480℃, and the treatment time is 500~800s. This molten salt temperature is a mixed phase region of bainite and pearlite. The lower the molten salt temperature, the closer it is to the peak precipitation temperature of quenched bainite. After the phase transformation, the quenched bainite transformation in the structure increases, the spacing between the troostite lamellae is finer, the proportion of tempered bainite in the complex phase structure increases, and the proportion of ferrite decreases. The strength of the wire rod increases and the plasticity decreases. However, if the molten salt temperature is too low, it is not conducive to the nucleation and tempering softening of troostite. If the proportion of tempered bainite is too large, the plasticity of the wire rod will be insufficient. On the contrary, if the molten salt temperature is higher, it is closer to the peak precipitation temperature of troostite. The proportion of tempered bainite in the complex phase structure decreases, the proportion of tempered troostite increases, the spacing between the lamellae becomes coarser, the strength of the wire rod decreases, and the plasticity increases. If the temperature is too high, it will be unfavorable for the formation of a small amount of quenched bainite, and the austenite will even transform into a pearlite structure with coarser lamellae, which will cause a large strength loss; the longer the treatment time, the more complete the transformation of austenite to quenched bainite and troostite with fine lamellar spacing, the lower the proportion of ferrite, the more the melted troostite, the lower the strength of the wire rod, the higher the plasticity, and the smaller the fluctuation of mechanical properties. However, if the treatment time is too long, the production efficiency will be affected, and excessive softening of the wire rod will be unfavorable for improving the strength of the wire rod. On the contrary, the shorter the treatment time, the lower the softening effect, resulting in a decrease in the plasticity of the wire rod. However, if the treatment time is too short, the complex phase structure cannot be softened, and even the residual austenite may affect the control of abnormal structure, resulting in a large plastic loss and increased fluctuation of the wire rod performance. Therefore, the molten salt temperature and treatment time can be further controlled to regulate the organizational state of the wire rod and the matching of strength and plasticity.
[0023] Since the cooling rate of the wire rod after online molten salt weak quenching isothermal treatment is relatively fast, in a preferred embodiment, the online molten salt weak quenching isothermal treatment is divided into a front-stage treatment and a back-stage treatment. The treatment time of the front-stage treatment is ≥30s, and the molten salt circulation volume of the front-stage treatment is greater than the molten salt circulation volume of the back-stage treatment. The use of a larger molten salt circulation volume in the front-stage treatment can promote faster cooling of the wire rod and further reduce the cooling rate and temperature difference from the outside to the inside of the wire rod cross section, which is beneficial to the formation of a troostite structure with fine lamellar spacing and can improve the uniformity of the structure. The molten salt circulation volume in the back-stage treatment is relatively smaller, which is more conducive to reducing production energy consumption when the treatment time is longer.
[0024] In a preferred embodiment, the molten salt circulation rate of the front-stage treatment is 550~750t / h, and the molten salt temperature rise is ≤10°C, so that the wire rod can quickly enter the mixed phase region of bainite and pearlite from the high-temperature austenite state after the front-stage treatment, further avoiding excessive molten salt temperature rise affecting the quenching bainite structure transformation.
[0025] In a preferred embodiment, the molten salt circulation rate of the post-stage treatment is 130~210t / h, and the molten salt temperature rise is ≤3°C. The temperature can be precisely controlled to promote the untransformed residual austenite after the previous stage treatment to continue to transform into fine lamellar spacing troostite and quenched bainite structure, reduce the ferrite content, and promote tissue tempering and lamellar melting transformation to regulate the strength and plasticity matching of the wire rod.
[0026] In a preferred embodiment, the roller slow cooling controls the wire rod to be cooled to below 300°C at a slow cooling rate of 0.15~0.35°C / s, which can avoid insufficient plasticity of the wire rod due to insufficient slow cooling. At the same time, slow cooling is used to promote further toughening of the wire rod structure and improve the tempering softening effect of the wire rod.
[0027] In a preferred embodiment, the roller slow cooling adopts a closed insulation cover, and the wire rod is transported into the insulation cover by the conveying roller, and the hot air from the online molten salt weak quenching isothermal treatment is blown to the conveying roller, so that the hot air thermal energy generated during the salt bath can be recycled, thereby reducing production energy consumption and avoiding transportation stagnation.
[0028] In a preferred embodiment, the roller speed of the conveying roller is 0.15~0.35m / s, and the hot air temperature is ≥250°C, which can meet the control of the slow cooling speed. At the same time, the roller speed is not too low to affect the production efficiency.
[0029] A low carbon and high strength multi-phase hot rolled wire rod for 1860 MPa grade stranded wire, the hot rolled wire rod is manufactured by any one of the above-mentioned methods for manufacturing low carbon and high strength multi-phase hot rolled wire rod for 1860 MPa grade stranded wire.
[0030] The hot-rolled wire rod is designed with C-Si-Mn composition that does not contain Cr and B, the composition can be further simplified, the material cost is lower, and the microstructure type is a complex phase structure composed of tempered troostite, tempered bainite, ferrite, and fused troostite. Compared with the traditional stranded steel wire rod structure composed of pearlite / troostite + ferrite structure layers, the interlamellar spacing of troostite is finer than pearlite, and the strength and drawing performance are better. After melting and spheroidizing to transform into tempered troostite and fused troostite, the organizational stress and dislocation density are further reduced, so that the plasticity can be further improved. At the same time, the complex phase structure also contains a small amount of tempered bainite. Compared with the stranded steel wire rod, bainite is regarded as an abnormal structure and the precipitation ratio is uncontrollable, or For high-strength wire rod with bainite structure as the main component, tempered bainite can utilize the high-strength characteristics of bainite. After tempering transformation, the stress, distortion and dislocation density of the organization are reduced, making the organization strong and tough. At the same time, the multiphase organization is mainly composed of tempered bainite and tempered bainite, which can reduce the proportion of ferrite and improve the strengthening effect of carbon element, thereby not only making up for the strength loss caused by reducing carbon content and eliminating hardenability alloy elements, but also further improving the matrix strength. Isothermal tempering is used to regulate the multiphase organization state of the tempered state, making the wire rod more plastic, avoiding the adverse effects of quenched bainite on plasticity and the risk of precipitation of abnormal martensite organization, and comprehensively improving the overall strength, plasticity and organization uniformity of the wire rod.
[0031] The finer the interlamellar spacing of the tempered troostite, the higher the wire rod strength, but this is accompanied by a decrease in molten salt temperature and thermodynamics, which is unfavorable for tempering softening and toughening. In a preferred embodiment, the interlamellar spacing of the tempered troostite is 80-110 nm.
[0032] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0. Avoiding network carbides can further improve the uniformity of the structure and the performance of the wire rod.
[0033] The hot-rolled wire rod has a more uniform structure, is free of network carbides and abnormal martensite structure, and has smaller fluctuations in mechanical properties. In a preferred embodiment, the same-circle difference in mechanical properties of the hot-rolled wire rod is ≤30 MPa.
[0034] In a preferred embodiment, the diameter of the hot-rolled wire rod is 7.0~12.5mm, the tensile strength is 1260~1310MPa, and the cross-sectional shrinkage rate is 42%~47%. The hot-rolled wire rod has higher tensile strength and good toughness, which makes it easier to reduce the number of drawing passes to achieve the target strength, thereby reducing plastic loss and reducing the risk of drawing and strand breakage in stranded wire production.
[0035] Compared with the prior art, the beneficial effects of the present invention are at least:
[0036] (1) In view of the current situation that the carbon content of the existing 1860MPa grade stranded wire is reduced, Cr, Mn, B and other elements are added to improve the hardenability, and the production of Stelmor wire leads to a high risk of abnormal structure, a weak cooling rate and weakened strengthening effect, which in turn causes an increased risk of stranded wire breakage during drawing. The manufacturing method of the present invention adopts a carbon chemical composition design combined with an online molten salt weak quenching isothermal technology process design. After spinning, the wire rod is controlled to quickly enter the mixed phase region of bainite and pearlite from the high temperature austenite state, which can refine the cementite carbide and form a quenched bainite-based The structure is mainly composed of a complex phase of bainite and bainite with a large interlamellar spacing, reducing the proportion of ferrite, compensating for the strength loss caused by reducing the carbon content and eliminating the hardenability component, while promoting the formed quenched bainite and bainite structures to undergo long-term isothermal tempering, and inducing the melting transformation of some bainite lamellae, and using the tempered state to regulate the structure of the bainite structure to become both strong and tough, so as to regulate the strength and plasticity matching of the wire rod, and using roller slow cooling to promote further toughening of the wire rod structure, thereby improving the overall strength and plasticity from the outside to the inside on the same section of the wire rod, avoiding brittle fracture of coiling, and having good industrial adaptability.
[0037] (2) In view of the current situation that the cost of hot-rolled wire rods for 1860MPa grade stranded wire is high and the strength and plasticity are difficult to match, the hot-rolled wire rod of the present invention adopts C-Si-Mn composition without Cr and B, and the microstructure type is a complex phase structure composed of tempered bainite, tempered bainite, ferrite and fused bainite, which can make the proportion of tempered bainite and tempered bainite more controllable, reduce the stress and dislocation density of the structure, and avoid the abnormal martensitic structure, so as to achieve high strength and plasticity matching, make the structure more suitable for deep drawing, and can achieve a tensile strength of 1260~1310MPa and a cross-sectional shrinkage rate of 42%~47%. It is used in the application fields of manufacturing 1860MPa grade stranded wire, with lower material cost and mechanical property fluctuations, better strength and plasticity, and can reduce the risk of wire breakage during stranded wire drawing after increasing the area reduction rate and drawing speed in stranded wire manufacturing, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0039] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0040] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0041] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0043] A preferred embodiment of the method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.72%, Si: 0.5%, Mn: 0.82%, P: 0.015%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0044] The rolling process is used to heat the steel billet with a specification of 180mm×180mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plastic, avoid decarburization and growth of original austenite crystals, and roll the steel billet into a wire with a diameter of 7mm through a rolling line after the steel billet comes out of the heating furnace, control the rolling temperature and reduction, avoid decarburization, increase the deformation and rolling speed, and refine the grains. Specifically: the heating temperature of the heating furnace is controlled to be ≤1090°C, the furnace time is 4h, the initial rolling temperature is 1060°C, the initial rolling reduction is 33%, the final rolling temperature is 945°C, and the final rolling reduction is 36%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The higher wire-spinning temperature provides favorable conditions for obtaining a larger temperature gradient. Specifically: the wire-spinning temperature is controlled to be 920°C.
[0045] The online molten salt weak quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and enters the mixed phase area of bainite and pearlite from the austenite state, inhibits the peak precipitation of tertiary cementite, refines cementite carbides, promotes the transformation of high-temperature austenite to form a structure dominated by quenched bainite and troostite complex phases, and then conveyed by a roller through the second stage salt bath tank for back-end treatment, with precise temperature control, promoting the untransformed residual austenite to continue to It is continuously transformed into quenched bainite and troostite structure, while promoting the tempering softening of quenched bainite and troostite, inducing the melting transformation of some troostite lamellae, and adjusting the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front-end treatment and the back-end treatment is 480℃, the treatment time of the front-end treatment is 30s, the molten salt circulation volume is 550t / h, and the molten salt temperature rise is ≤10℃; the treatment time of the back-end treatment is 470s, the molten salt circulation volume is 130t / h, and the molten salt temperature rise is ≤3℃, that is, the online molten salt weak quenching isothermal treatment time is 500s.
[0046] The roller slow cooling process adopts closing the insulation cover, and the wire rod coming out of the second salt bath tank is transported into the insulation cover by the conveying roller for slow cooling treatment. At the same time, the hot air ≥250°C above the two salt bath tanks is blown to the conveying roller to avoid insufficient cooling and reduce the plasticity of the wire rod. At the same time, the slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is transported at a roller speed of 0.35m / s, and the wire rod is controlled to be cooled to 295°C at a slow cooling speed of 0.35℃ / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 As shown, its microstructure is 68% tempered bainite + 26% tempered bainite + 4% ferrite + 2% fused bainite by volume, the interlamellar spacing of tempered bainite is 110nm, the network carbide grade is level 0, the mechanical property difference is 25MPa, the tensile strength is 1260MPa, and the section shrinkage rate is 47%.
[0047] Comparative Example 1:
[0048] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor strong air cooling → roller slow cooling, specifically: the heating temperature of the heating furnace is controlled to be ≤1020°C, the furnace time is 5h, the initial rolling temperature is 985°C, the final rolling temperature is 870°C, and the spinning temperature is 840°C; the Stelmor strong air cooling adopts an air volume of 200,000 m per fan 3 / h, open 1~7# fans at 85%, cool the wire rod to 645℃ at a cooling rate of 8.4℃ / s, and slow cool the roller by closing the fan and covering the heat preservation cover, cool the wire rod to 290℃ at a cooling rate of 0.9℃ / s. The hot-rolled wire rod is obtained after it comes off the line. Its microstructure is 86% pearlite + 14% ferrite by volume, the pearlite lamellar spacing is 189nm, the network carbide grade is 1, the mechanical property difference is 61MPa, the tensile strength is 1146MPa, and the cross-sectional shrinkage rate is 33%.
[0049] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the Stelmor air-cooling phase transformation process, the cooling rate is slow, resulting in coarser pearlite lamellae and a higher proportion of ferrite, which weakens the strengthening effect. Due to uncontrollable segregation and cooling rate, the organization is not uniform, there is network carbon, and the mechanical properties fluctuate greatly. After the incubation period is extended, the organization stress and dislocation density are high, and the plasticity is insufficient. The present invention adopts carbon chemical composition design combined with online molten salt weak quenching isothermal technology process design to refine cementite carbides and form a structure dominated by quenched bainite and fine lamellar spacing troostite complex phases, reduce the proportion of ferrite, and make the proportion of tempered troostite and tempered bainite more controllable. Isothermal tempering is used to reduce organization stress and dislocation density, which can significantly improve the tensile strength and cross-sectional shrinkage rate of the wire rod. At the same time, the mechanical properties fluctuate less, which is beneficial to reduce the risk of wire breakage during the production of 1860MPa grade stranded wire.
[0050] Comparative Example 2:
[0051] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating temperature of the heating furnace is controlled to be ≤1075°C, the furnace time is 4.5h, the initial rolling temperature is 1050°C, the final rolling temperature is 930°C, the spinning temperature is 905°C, the online molten salt weak quenching isothermally controlled wire rod is cooled at a cooling rate of 37°C / s, and the hot-rolled wire rod finished product is obtained after it is offline. Embodiment 2:
[0052] A preferred embodiment of the method for manufacturing a low-carbon, high-strength, multi-phase hot-rolled wire rod for 1860MPa grade stranded wire according to the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.7%, Si: 0.65%, Mn: 0.72%, P: 0.013%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0053] The rolling process is used to heat the steel billet with a specification of 180mm×180mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plastic, avoid decarburization and growth of original austenite crystals, and roll the steel billet into a wire with a diameter of 8.5mm through a rolling line after the steel billet comes out of the heating furnace, control the rolling temperature and reduction, avoid decarburization, increase the deformation and rolling speed, and refine the grains. Specifically: the heating temperature of the heating furnace is controlled to be ≤1095°C, the furnace time is 3.5h, the initial rolling temperature is 1070°C, the initial rolling reduction is 31%, the final rolling temperature is 950°C, and the final rolling reduction is 32%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The higher wire-spinning temperature provides favorable conditions for obtaining a larger temperature gradient. Specifically: the wire-spinning temperature is controlled to be 925°C.
[0054] The online molten salt weak quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and enters the mixed phase area of bainite and pearlite from the austenite state, inhibits the peak precipitation of tertiary cementite, refines cementite carbides, promotes the transformation of high-temperature austenite to form a structure dominated by quenched bainite and troostite complex phases, and then conveyed by a roller through the second stage salt bath tank for back-end treatment, with precise temperature control, promoting the untransformed residual austenite to continue to The steel wire rod is continuously transformed into quenched bainite and troostite structure, while promoting the tempering softening of quenched bainite and troostite, inducing the melting transformation of some troostite lamellae, and adjusting the strength-plasticity matching of the wire rod. Specifically, the molten salt temperature of the front-end treatment and the back-end treatment is 467°C, the treatment time of the front-end treatment is 40s, the molten salt circulation volume is 600t / h, and the molten salt temperature rise is ≤10°C; the treatment time of the back-end treatment is 670s, the molten salt circulation volume is 180t / h, and the molten salt temperature rise is ≤3°C, that is, the online molten salt weak quenching isothermal treatment time is 710s.
[0055] The roller slow cooling process adopts closing the insulation cover, and the wire rod coming out of the second salt bath tank is transported into the insulation cover by the conveying roller for slow cooling treatment. At the same time, the hot air ≥250°C above the two salt bath tanks is blown to the conveying roller to avoid insufficient cooling and reduce the plasticity of the wire rod. At the same time, the slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is transported at a roller speed of 0.26m / s, and the wire rod is controlled to be cooled to 296°C at a slow cooling rate of 0.23℃ / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0056] Comparative Example 3:
[0057] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: the online molten salt weak quenching isothermally controlled wire rod is cooled at a cooling rate of 41°C / s, the molten salt temperature of the front-end treatment and the back-end treatment is 415°C, and the hot-rolled wire rod finished product is obtained after going offline.
[0058] Comparative Example 4:
[0059] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: the online molten salt weak quenching isothermally controlled wire rod is cooled at a cooling rate of 37°C / s, the molten salt temperature of the front-end treatment and the back-end treatment is 490°C, and the hot-rolled wire rod finished product is obtained after going offline. Embodiment 3:
[0060] A preferred embodiment of the method for manufacturing a low-carbon, high-strength, multi-phase hot-rolled wire rod for 1860MPa grade stranded wire according to the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.73%, Si: 0.61%, Mn: 0.79%, P: 0.013%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0061] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, avoid decarburization and growth of original austenite crystals, and roll the steel billet into a wire with a diameter of 11mm through a rolling line after the steel billet comes out of the heating furnace, control the rolling temperature and reduction, avoid decarburization, increase the deformation and rolling speed, and refine the grains. Specifically: the heating temperature of the heating furnace is controlled to be ≤1100°C, the time in the furnace is 3.5h, the initial rolling temperature is 1080°C, the initial rolling reduction is 28%, the final rolling temperature is 955°C, and the final rolling reduction is 30%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The higher wire-spinning temperature provides favorable conditions for obtaining a larger temperature gradient. Specifically: the wire-spinning temperature is controlled to be 930°C.
[0062] The online molten salt weak quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and enters the mixed phase area of bainite and pearlite from the austenite state, inhibits the peak precipitation of tertiary cementite, refines cementite carbides, promotes the transformation of high-temperature austenite to form a structure dominated by quenched bainite and troostite complex phases, and then conveyed by a roller through the second stage salt bath tank for back-end treatment, with precise temperature control to promote the untransformed residual austenite to continue to The steel rod is continuously transformed into quenched bainite and troostite structure, while promoting the tempering softening of quenched bainite and troostite, inducing the melting transformation of some troostite lamellae, and adjusting the strength-plasticity matching of the wire rod. Specifically, the molten salt temperature of the front-end treatment and the back-end treatment is 446°C, the treatment time of the front-end treatment is 50s, the molten salt circulation volume is 700t / h, and the molten salt temperature rise is ≤10°C; the treatment time of the back-end treatment is 750s, the molten salt circulation volume is 195t / h, and the molten salt temperature rise is ≤3°C, that is, the online molten salt weak quenching isothermal treatment time is 800s.
[0063] The roller slow cooling process adopts closing the insulation cover, and the wire rod coming out of the second salt bath tank is transported into the insulation cover by the conveying roller for slow cooling treatment. At the same time, the hot air ≥250°C above the two salt bath tanks is blown to the conveying roller to avoid insufficient cooling and reduce the plasticity of the wire rod. At the same time, the slow cooling promotes the further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is transported at a roller speed of 0.31m / s, and the wire rod is controlled to be cooled to 284°C at a slow cooling rate of 0.27℃ / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0064] Comparative Example 5:
[0065] A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the processing time of the front-end treatment of the online molten salt weak quenching isothermal treatment is 40s, and the processing time of the rear-end treatment is 410s, that is, the online molten salt weak quenching isothermal treatment time is 450s, and the hot-rolled wire rod finished product is obtained after going offline.
[0066] Comparative Example 6:
[0067] A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the processing time of the front-end treatment of the online molten salt weak quenching isothermal treatment is 60s, and the processing time of the back-end treatment is 840s, that is, the online molten salt weak quenching isothermal treatment time is 900s, and the hot-rolled wire rod finished product is obtained after going offline. Embodiment 4:
[0068] A preferred embodiment of the method for manufacturing a low-carbon, high-strength, multi-phase hot-rolled wire rod for 1860MPa grade stranded wire according to the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.74%, Si: 0.57%, Mn: 0.84%, P: 0.014%, S: 0.015%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt weak quenching isothermal → roller slow cooling → coiling, specifically:
[0069] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, avoid decarburization and growth of original austenite crystals, and roll the steel billet into a wire with a diameter of 12.5mm through a rolling line after the steel billet comes out of the heating furnace, control the rolling temperature and reduction, avoid decarburization, increase the deformation and rolling speed, and refine the grains. Specifically: the heating temperature of the heating furnace is controlled to be ≤1110°C, the furnace time is 3h, the initial rolling temperature is 1085°C, the initial rolling reduction is 25%, the final rolling temperature is 960°C, and the final rolling reduction is 28%; the wire-spinning process is used to convert the wire coming out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. The higher wire-spinning temperature provides favorable conditions for obtaining a larger temperature gradient. Specifically: the wire-spinning temperature is controlled to be 935°C.
[0070] The online molten salt weak quenching isothermal process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 41°C / s, and enters the mixed phase area of bainite and pearlite from the austenite state, inhibits the peak precipitation of tertiary cementite, refines cementite carbides, promotes the transformation of high-temperature austenite to form a structure dominated by quenched bainite and troostite complex phases, and then conveyed by a roller through the second stage salt bath tank for back-end treatment, with precise temperature control, promoting the untransformed residual austenite to continue to The steel wire is continuously transformed into quenched bainite and troostite structures, while promoting the tempering softening of quenched bainite and troostite, inducing the melting transformation of some troostite lamellae, and adjusting the strength-plasticity matching of the wire rod. Specifically, the molten salt temperature of the front-end treatment and the back-end treatment is 425°C, the treatment time of the front-end treatment is 35s, the molten salt circulation volume is 750t / h, and the molten salt temperature rise is ≤10°C; the treatment time of the back-end treatment is 605s, the molten salt circulation volume is 210t / h, and the molten salt temperature rise is ≤3°C, that is, the online molten salt weak quenching isothermal treatment time is 640s.
[0071] The roller slow cooling process adopts closing the insulation cover, and the wire rod coming out of the second salt bath tank is transported into the insulation cover by the conveying roller for slow cooling treatment. At the same time, the hot air ≥250°C above the two salt bath tanks is blown to the conveying roller to avoid insufficient cooling and reduce the plasticity of the wire rod. At the same time, the slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is transported at a roller speed of 0.15m / s, and the wire rod is controlled to be cooled to 275°C at a slow cooling speed of 0.15℃ / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0072] Comparative Example 6:
[0073] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the roller slow cooling process adopts a closed insulation cover, conveys the wire rod at a roller speed of 0.45m / s, controls the wire rod to be cooled to 280°C at a slow cooling rate of 0.9°C / s, and obtains the hot-rolled wire rod finished product after it comes off the line.
[0074] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below:
[0075] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods
[0076]
[0077] It can be seen from the results of Examples 1 to 4 that the microstructure type of the hot-rolled wire rod of the present invention is a complex phase structure composed of tempered troostite, tempered bainite, ferrite, and fused troostite, which can achieve high strength and plasticity matching. The product reaches a tensile strength of 1260~1310MPa and a cross-sectional shrinkage rate of 42%~47%. It can be used in application fields such as manufacturing 1860MPa-grade stranded wire, adapting to the requirements of increasing the drawing speed and area reduction rate during stranded wire manufacturing, and can reduce the risk of wire breakage.
[0078] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the selection of a higher spinning temperature can not only obtain a larger temperature gradient through online molten salt micro-quenching treatment, thereby increasing the supercooling degree, which is beneficial to increasing the nucleation rate of troostite and refining the troostite lamella spacing, but also the rolling temperature can be higher, which is beneficial to improving the rolling speed and efficiency.
[0079] It can be seen from the results of Examples 1 to 4 that the lower the molten salt temperature, as the treatment time is extended, the quenched bainite transformation in the structure after the phase transformation increases, the spacing between the troostite lamellae is finer, the proportion of tempered bainite in the complex phase structure increases, the proportion of ferrite decreases, the strength of the wire rod increases, and the plasticity decreases. It can be seen from the comparison results of Example 2 and Comparative Example 3 that the molten salt temperature is too low, which is not conducive to the nucleation of troostite and tempering softening. If the proportion of tempered bainite is too large, the plasticity of the wire rod will be insufficient.
[0080] It can be seen from the results of Examples 1 to 4 that the higher the molten salt temperature, as the treatment time increases, the proportion of tempered bainite in the complex phase structure decreases, the proportion of tempered troostite increases, the interlamellar spacing becomes coarser, the wire rod strength decreases, and the plasticity increases. It can be seen from the comparison results of Example 2 and Comparative Example 4 that if the molten salt temperature is too high, it is not conducive to the formation of a small amount of quenched bainite, the tempered troostite lamellae become coarser, and soften too quickly, which will cause a large strength loss.
[0081] It can be seen from the results of Examples 1 to 4 that the shorter the treatment time of the molten salt weak quenching isothermal treatment of the wire, the smaller the proportion of molten troostite and the lower the softening effect. It can be seen from the comparison results of Example 3 and Comparative Example 5 that if the treatment time is too short and the multiphase structure is insufficiently softened, a large plastic loss will occur and the performance fluctuation of the wire rod will increase.
[0082] It can be seen from the results of Examples 1 to 4 that the longer the treatment time of the wire molten salt weak quenching isothermal treatment, the more complete the transformation of austenite to quenched bainite and fine lamellar interlayer troostite complex structure, the lower the proportion of ferrite, the more the fused troostite, the lower the strength of the wire rod, the higher the plasticity, and the smaller the fluctuation of mechanical properties. It can be seen from the comparison results of Example 3 and Comparative Example 6 that if the treatment time is too long, the wire rod will be excessively softened, which will be detrimental to improving the strength of the wire rod.
[0083] From the comparison results of Example 4 and Comparative Example 7, it can be seen that by closing the insulation cover and blowing the hot air of the online molten salt weak quenching isothermal treatment to the conveyor roller, the hot air thermal energy generated during the salt bath can be recycled, the generation energy consumption can be reduced, and the cooling rate of the wire rod can be further reduced. Slow cooling can be used to promote further toughening of the wire rod structure and improve the tempering softening effect of the wire rod.
[0084] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.70%~0.74%, Si: 0.5%~0.65%, Mn: 0.72%~0.84%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥920°C, it is subjected to an online molten salt weak quenching isothermal treatment, so that the wire rod is cooled at a cooling rate of ≥38°C / s, and enters a mixed phase of bainite and pearlite from an austenite state. zone, forming a structure dominated by quenched bainite and troostite complex phases, and isothermally tempered at the same time to promote the tempering softening of quenched bainite and troostite, induce the melting transformation of some troostite lamellae, and finally slowly cooled by rollers to form a hot-rolled wire rod with a microstructure including 62% to 68% by volume of tempered troostite, 26% to 33% by volume of tempered bainite, and the rest being a complex phase structure composed of ferrite and melted troostite; the molten salt temperature of the online molten salt weak quenching isothermal treatment is 425 to 480°C, and the treatment time is 500 to 800s.
2. The method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 1, characterized in that: Before the rolling, the heating temperature of the heating furnace is controlled to be ≤1110°C and the time in the furnace is ≤4h.
3. The method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1060-1085° C., the initial rolling reduction is 25%-33%, the final rolling temperature is ≥945° C., and the final rolling reduction is 28%-36%.
4. The method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire according to claim 1, characterized in that: The online molten salt weak quenching isothermal treatment is divided into a front-end treatment and a back-end treatment. The treatment time of the front-end treatment is ≥30s, the molten salt circulation volume is 550~750t / h, and the molten salt temperature rise is ≤10°C; the molten salt circulation volume of the back-end treatment is 130~210t / h, and the molten salt temperature rise is ≤3°C.
5. The method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 1, characterized in that: The roller slow cooling controls the wire rod to be cooled to below 300° C. at a slow cooling rate of 0.15-0.35° C. / s.
6. The method for manufacturing the low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 5, characterized in that: The roller slow cooling adopts a closed heat preservation cover, the wire rod is transported into the heat preservation cover by the conveying roller, and the hot air of the online molten salt weak quenching isothermal treatment is blown to the conveying roller.
7. A low-carbon high-strength multi-phase hot-rolled wire rod for 1860MPa grade stranded wire, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing low-carbon and high-strength complex-phase hot-rolled wire rod for 1860 MPa grade stranded wire as described in any one of claims 1 to 6.
8. The low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 80-110 nm, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤30 MPa.
9. The low-carbon high-strength multi-phase hot-rolled wire rod for 1860 MPa grade stranded wire according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 7.0-12.5 mm, a tensile strength of 1260-1310 MPa, and a cross-sectional shrinkage of 42%-47%.
Citation Information
Patent Citations
Low-carbon, high-strength, and high-toughness steel strand wire rod and its manufacturing process
CN104789880B
Isothermal quenching heat treatment process and device for steel wire
CN108103304A
800 MPa-grade high-toughness weather-resistant thick steel plate and preparation method thereof
CN110241357A